Systematic Review and Network Meta-Analysis of Bevacizumab Plus First-Line Topotecan-Paclitaxel or Cisplatin-Paclitaxel Versus Non–Bevacizumab-Containing Therapies in Persistent, Recurrent, or Metastatic Cervical Cancer. Issue 6 (July 2017) - Rosen, Virginia M.; Guerra, Ines; McCormack, Mary; Nogueira-Rodrigues, Angélica; Sasse, Andre; Munk, Veronica C.; Shang, Aijing
Abstract : Objective: Despite advances in cervical cancer prevention and diagnosis, outcomes for patients given a diagnosis of advanced and recurrent disease are poor. In the GOG240 trial, the addition of bevacizumab to paclitaxel-topotecan or paclitaxel-cisplatin has been shown to prolong survival compared with paclitaxel-topotecan or paclitaxel-cisplatin in patients with persistent, recurrent, or metastatic disease. However, standards of care vary between regions and countries. The purpose of this systematic review and network meta-analysis was to enable a comparison between bevacizumab + chemotherapy with multiple monotherapy or combination chemotherapy regimens in the treatment for women with advanced, recurrent, or persistent cervical cancer. Methods/Materials: A systematic literature review was conducted to identify randomized or nonrandomized controlled trials of patients with recurrent, persistent, or metastatic cervical cancer published in English from 1999 to 2015. A feasibility study was performed to assess the heterogeneity of the trials, and a network meta-analysis was conducted. Fixed- and random-effects models were fitted to calculate the hazard ratio for overall survival (OS) for all pairwise comparisons and ranking of all interventions. Results: Twenty-three studies (19 trials) met inclusion criteria and were included in the review. Sample sizes ranged from 69 to 452, and median patient age ranged from 45 to 53 years. There was a trend toward prolonged OS with cisplatin-paclitaxel-bevacizumab and topotecan-paclitaxel-bevacizumab compared with all non–bevacizumab-containing therapies. Cisplatin-paclitaxel-bevacizumab had the highest probability of being the most efficacious compared with all regimens (68.1%), and cisplatin monotherapy had the lowest (0%). Conclusions: The results of this network meta-analysis show that bevacizumab in combination with paclitaxel-topotecan or paclitaxel-cisplatin is likely to prolong OS over other non–bevacizumab-containing chemotherapies (eg, paclitaxel-carboplatin), which were not included in the GOG240 trial. In patients with advanced, persistent, and recurrent cervical cancer, cisplatin-paclitaxel-bevacizumab and topotecan-paclitaxel-bevacizumab showed the highest efficacy in all regimens investigated in this analysis. Abstract : Supplemental digital content is available in the text.